Slip flow of nanofluids between parallel plates heated with a constant heat flux - Öztürk, Ayşegül (Strojniški vestnik, 2016)
This study investigates the steady fully developed laminar flow and heat transfer of nanofluids between parallel plates heated with a constant heat flux. The governing equations were solved analytically under the boundary conditions of slip velocity and temperature jump. Water was taken as the base fluid and Cu, CuO and Al 2 O 3 as the nanoparticles. The results were obtained for the slip factor in the range of 0 to 0.04, for the Brinkman number in the range of -0.1 to 0.1, for three different values of the ratio of the liquid layering thickness to the particle radius (0.1, 0.2, and 0.4) and for the solid volume fraction ranging from 0 % to 8 %. The results show that the nanoparticle presence in the base fluid has a significant effect on both the velocity field and heat-transfer characteristics. The average Nusselt number increases considerably with the increase of the nanoparticle solid volume fraction. The average Nusselt number takes much higher values for high values of the ratio of the liquid layering thickness to the nanoparticle radius. The average heat transfer rate of nanofluids between parallel plates ranges from the highest to the lowest when Cu, Al2 O3, and CuO are used as nanoparticles, respectively.
Keywords: drseči tok; faktor drsenja; nanofluidi; nanotekočine; Nusseltovo število; vzporedna plošča